CITIZENSHIP EDUCATION IN EUROPEAN SCHOOL SYSTEMS - Maria-Corina POPA (National Centre for Policy and Evaluation in Education, 2023)
This paper aims to open a reflective framework, that should be useful to the Romanian education system and encompass ways in which citizenship education is studied in other European countries, at primary and secondary levels. In this regard, the article presents the characteristics of the school systems which are based on maximalist and minimalistic approaches to citizenship education, the critical approaches to citizenship education and, consequently, the concept of "critical citizenship". The article also includes a brief timeline of legislative and public policy efforts at European level to support education for democratic citizenship, starting from the Maastricht Treaty and reaching the "Reference Framework of Competences for Democratic Culture". Last but not least, the paper will highlight a series of reforms and approaches to citizenship education at European level (as a separate or integrated school subject, or in a crosscurricular perspective), that references the latest Eurydice study on citizenship education in European schools.